Non-Oil Export and Exchange Rate Nexus in Nigeria: Another Empirical Verification - Orji, Anthony; Abubakar, Mohammed; Ogbuabor, Jonathan E; Anthony-Orji, Onyinye I; Ojonta, Obed I (Growth, 2021)
This study examined the nexus between Exchange Rate and Non-Oil Export in Nigeria using time series data from 1985 to 2018. Secondary data were sourced from the Central Bank of Nigeria (CBN), National Bureau of Statistics (NBS) and World Bank Development Indicators (WDI). The study adopted Autoregressive Distributed Lag (ARDL) model and it was fitted with Seven variables; namely, Non-oil Export (NOE), Exchange Rate (EXR), Credit to Private Sector (CPS), Trade Openness (OPN), Inflation (INF), Interest Rate (INT) and Foreign Direct Investment (FDI). The results showed that the exchange rate has a positive and significant impact on non-oil export in Nigeria. Therefore, the study recommended that the Government should encourage international trade to boost non-oil export and increase foreign exchange earnings. Also, there is a need for the government to improve the financial institutions to make investment funds available. Lastly, there is a need to revisit the export-oriented policy to ensure that the non-oil sector is well catered for.